UPAYA UKRAINA BERGABUNG DENGAN UNI EROPA DI MASA PEMERINTAHAN VOLODYMYR ZELENSKY - ', Salsabila; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research discusses the efforts made by Ukraine to fulfill the political, economic and acquis criteria to become a candidate country for European Union membership under the leadership of President Volodymyr Zelensky. Zelensky's efforts cannot be separated from the demands of the Ukrainian people and global conditions. This research uses the country level of analysis with the constructivism theory of Alexander Wendt. Alexander Wendt argued that a society will establish a common identity through cooperation and belief in the same values. The values possessed by society shape public opinion which influences political references which influence state policy making. The results of this research show that the Ukrainian people identify themselves as having the same values as the European Union (EU), namely the values of democracy and freedom, these values influence the political references of the Ukrainian people to have a pro-EU president. When Ukraine was led by a pro-Russian president, the Euromaidan revolution and the Orange revolution occurred which demanded a change of president. When in the 2019 election, Volodymyr Zelensky, who was a pro-EU candidate, was elected president of Ukraine, during his leadership Ukraine came under attack from Russia which increased Ukraine's demands to join the EU. With the Ukrainian people demanding to join the EU, Zelensky is making efforts to fulfill the criteria as a potential candidate country. In the political field, Zelensky made the Eastern Ukraine region a gray area militarily controlled by Russia but politically controlled by Ukraine. This agreement with Russia aims to make Ukrainian politics more stable. In the economic sector, Ukraine implemented a number of policies that allow investment to open up a free market and in the acquis sector, Ukraine ratified a number of European Union laws to become national laws. However, based on the assessment carried out by the European Union in 2022-2023, Ukraine is not yet worthy of becoming a candidate country for the European Union. Keywords: Ukraine, Rational Actor, European Union, economy, politics, acquis